Effect of vitamin D supplementation on lung function in chronic obstructive pulmonary disease patients: An evidence-based case report - Kirana, Annisa Nurul; Sunardi, Diana (World Nutrition Journal, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is characterized by progressive and persistent airflow obstruction together with an increased chronic inflammatory response, primarily caused by environmental exposure and smoking habit. Vitamin D deficiency is associated with increased rates of exacerbation and hospitalization in COPD patients. Recent studies have indicated a direct correlation between vitamin D deficiency and the severity of COPD, suggesting that acute exacerbation could be prevented with vitamin D supplementation. Some studies propose that correcting the serum vitamin D level may improve the prognosis for COPD patients experiencing respiratory tract infections. Objective: The aim of this study was to determine the effect of vitamin D supplementation for lung function in COPD patient. Methods: Literature search was carried out by advanced searching on Pubmed, Cochrane Library, and Scopus using a combination of MeSH Terms and Title/Abstract. Following screening for duplications, the literature obtained then screened according to predetermined eligibility criteria. The appropriate literatures were critically reviewed and the level of evidence in accordance with the Oxford Center for Evidence Based Medicine. Results: One meta-analysis and three randomized controlled trial (RCT) met the PICO and eligibility criteria that had been set. Three studies concluded that vitamin D supplementation enhanced lung function in COPD patient. Vitamin D deficiency is common in COPD patients, so it is recommended to check vitamin D levels before vitamin D supplementation. Conclusion: Vitamin D administration can improve lung function and prevent acute exacerbation in COPD patients.